2011
DOI: 10.1021/es201224x
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-Dependent Isotope Fractionation during Aerobic and Anaerobic Degradation of Monochlorobenzene and 1,2,4-Trichlorobenzene

Abstract: Stable carbon isotope fractionation is a valuable tool for monitoring natural attenuation and to establish the fate of groundwater contaminants. In this study, we measured carbon isotope fractionation during aerobic and anaerobic degradation of two chlorinated benzenes: monochlorobenzene (MCB) and 1,2,4-trichlorobenzene (1,2,4-TCB). MCB isotope fractionation was measured in anaerobic methanogenic microcosms, while 1,2,4-TCB isotope experiments were carried out in both aerobic and anaerobic microcosms. Large is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(81 citation statements)
references
References 53 publications
7
73
1
Order By: Relevance
“…Kaschl et al [24,27] demonstrated MCB anaerobic biodegradation at two contaminated sites, while [28] investigated anaerobic biodegradation of dichlorobenzenes (DCBs) and MCB by interpreting CSIA results on the basis of an isotope mass balance approach. On the contrary, almost no isotope carbon fractionation for MCB and 1,2,4 TCB during aerobic biodegradation was demonstrated [23,24] -results that were confirmed by Liang et al [25]. Thus, the lack of carbon isotope fractionation limits the use of carbon-CSIA for MNA applications in contaminated environments under oxic conditions.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Kaschl et al [24,27] demonstrated MCB anaerobic biodegradation at two contaminated sites, while [28] investigated anaerobic biodegradation of dichlorobenzenes (DCBs) and MCB by interpreting CSIA results on the basis of an isotope mass balance approach. On the contrary, almost no isotope carbon fractionation for MCB and 1,2,4 TCB during aerobic biodegradation was demonstrated [23,24] -results that were confirmed by Liang et al [25]. Thus, the lack of carbon isotope fractionation limits the use of carbon-CSIA for MNA applications in contaminated environments under oxic conditions.…”
Section: Introductionmentioning
confidence: 84%
“…Although a reactive transport model is needed for a conclusive δ 13 C MCB data interpretation, some further reasoning can be inferred. An enriched δ 13 C MCB value of −28.3‰ compared to δ 13 C DCBs values ranging from −29.3‰ to −31.0‰ leads to hypothesizing further anaerobic MCB degradation to benzene in the vicinity of S70T [25]. On the contrary, where δ 13 C MCB values remained depleted compared to δ 13 C DCBs values (S80 and S67T), local anaerobic biodegradation of MCB is not likely to be occurring.…”
Section: Biodegradationmentioning
confidence: 96%
See 2 more Smart Citations
“…0.2 ml headspace samples were used for benzene measurement as described before [345], and 1 ml liquid samples were used for the detection of CBs. Liquid samples were extracted with 400 µl hexane by overnight shaking at 600 rpm followed by 100 analysis was performed with NG-Tax, an in-house pipeline [346] in which operational taxonomic units (OTUs) were assigned to taxonomy using uclust [347] in an open reference approach against the SILVA 16S rRNA gene reference database [348].…”
Section: Detection Of Benzene and Chlorinated Benzenesmentioning
confidence: 99%